Estudio del efecto de la adición sostenida de nitrógeno sobre la diversidad microbiana del suelo en el bosque montano del sur de Ecuador - Samaniego Zúñiga, Maritza del Rocío (2015)
Tropical ecosystems are receiving an elevated amount of reactive nitrogen via atmospheric depositions that result from antropogenic perturbations and climate changes. In the last decades, many efforts have tried to unravel the effects that elevated concentrations of nitrogen in the soil might have on fungal and bacterial communities. Is now widely accepted that nitrogen excess changes the dynamic of microbial communities and affects their metabolic profiles. However, we are still far from knowing what happens at the level of individual species. In the present work we describe changes at the species level that took place on soils of the Tropical Mountain Forest of Southern Ecuador as part of a long term nitrogen manipulation experiment. To do so, we carried out the in vitro cultivation of fungal and baterial species together with their molecular characterization. The obtained results shed light on relevant aspects of how the dynamics of the studied ecosystem is being affect by the excess of nitrogen, this through the identification of key microbial players.